2011
DOI: 10.1016/j.jcf.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in adolescents with CF and their caregivers

Abstract: Screening for anxiety/depression and addressing mental health issues within the framework of a family perspective is recommended as an element of routine healthcare for adolescents with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 41 publications
1
37
0
4
Order By: Relevance
“…The highest values were perceived on the dimension satisfaction with the family, which is consistent with results of other investigations of families with other chronic conditions (e.g. [7,31]). This indicates that they feel comfortable with the support they have from their partner or friends, but feel restricted in developing their personal interests.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The highest values were perceived on the dimension satisfaction with the family, which is consistent with results of other investigations of families with other chronic conditions (e.g. [7,31]). This indicates that they feel comfortable with the support they have from their partner or friends, but feel restricted in developing their personal interests.…”
Section: Discussionsupporting
confidence: 90%
“…The lowest quartile ( Q .25 ), which splits off the lowest 25% of the data, was selected by the authors as the cut-off for being at risk of impaired or poor PQoL. This cut-off was chosen arbitrarily based on existing literature which suggests that about 20 to 30% of parents who have children with chronic conditions require psychosocial support or treatment (e.g., the international TIDES study [30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…Depression, in particular, is linked to worse health outcomes, including quality of life and lung function [106,113,114]. The mechanism of this relationship is likely multifactorial, including decreased adherence and self-management, which are affected negatively by depression [115].…”
Section: Psychological Functioningmentioning
confidence: 99%
“…Association of depression and anxiety with declining health outcomes of CF has been a major focus in recent years. Several cross-sectional studies have consistently shown that CF patients with anxiety, depression, or both exhibit worsened lung function, nutritional status, and overall quality of life [102][103][104][105]. Specifically, those afflicted with chronic lung conditions and some form of a psychiatric disorder tend to show patterns of worse symptoms and greater functional impairment than those without [106].…”
Section: Cf-related Mental Impairmentsmentioning
confidence: 99%